Bark Characteristics of Acacia auriculiformis A. Cunn. ex Benth. and Acacia mangium Willd. From Industrial Plantation Forest - Sri Mutiar; Anwar Kasim; Emriadi; Alfi Asben (Foresty Faculty of Hasanuddin University, 2020)
Increasing the value of bark can be known through the characteristics of the bark such as physical properties, the grade of fiber quality and the chemical composition of the bark. The purpose of this study is to find out the characteristics of the bark of the acacia plant species (i.e. Acacia auriculiformis and Acacia mangium) of Industrial Plantation Forest. The characteristics of the bark observed includes physical properties, quality grade of fiber and chemical composition. The results of this study showed that the bark density, thickness and water content of A. auriculiformis were 1.18g/cm3, 1.55 mm and 35.27% respectively, while, the bark density, thickness and water content of A. mangium were 0.95 g/cm3, 1.23 mm and 48.21% respectively. The fiber qualities of both plants are classified as grade III. The extractive substance levels of A. auriculiformis and A. mangium were 23.06% and 20.63%, respectively. Based on the analysis with GCMS it can be seen that the main compounds dissolve-hexane from species A. auriculiformis were 2-phenyl phenol 33.6% and palmitic acid 13.5%. In the species A. mangium the main compounds soluble n-hexane were palmitic acid 28.97% and oleic acid 21.43%. The results of the analysis showed that these two bark species could potentially to be adhesives materials, tanning agent, particle boards, and inhibitors at the rate of corrosion of steel.